2013
DOI: 10.1177/0269216313510341
|View full text |Cite
|
Sign up to set email alerts
|

Place of death and end-of-life transitions experienced by very old people with differing cognitive status: Retrospective analysis of a prospective population-based cohort aged 85 and over

Abstract: Background: Despite fast-growing 'older old' populations, 'place of care' trajectories for very old people approaching death with or without dementia are poorly described and understood. Aim: To explore end-of-life transitions of 'older old' people across the cognitive spectrum. Design: Population-based prospective cohort (United Kingdom) followed to death. Setting/participants: Mortality records linked to 283 Cambridge City over-75s Cohort participants' cognitive assessments <1 year before dying aged ≥85 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 63 publications
1
40
0
3
Order By: Relevance
“…For the other countries, one possible explanation might be that older people with dementia who are more highly educated, or married, as well as those aged 65 to 79 and men in general, are more likely to reside at home, but are unable to remain there until the very end of life, resulting in an end-of-life hospital admission and hospital death. 9,36,38 One Dutch study found that for older people, 2 main scenarios were likely: residing in a nursing home, lowering the chances of hospital death, or staying at home as long as possible, with a higher likelihood of hospital death. 39 Consequently, it could be suggested that among older people with dementia, those who are most likely to reside at home, in particular, should be supported by specialist palliative care services to reduce the number of hospital deaths.…”
Section: Discussionmentioning
confidence: 99%
“…For the other countries, one possible explanation might be that older people with dementia who are more highly educated, or married, as well as those aged 65 to 79 and men in general, are more likely to reside at home, but are unable to remain there until the very end of life, resulting in an end-of-life hospital admission and hospital death. 9,36,38 One Dutch study found that for older people, 2 main scenarios were likely: residing in a nursing home, lowering the chances of hospital death, or staying at home as long as possible, with a higher likelihood of hospital death. 39 Consequently, it could be suggested that among older people with dementia, those who are most likely to reside at home, in particular, should be supported by specialist palliative care services to reduce the number of hospital deaths.…”
Section: Discussionmentioning
confidence: 99%
“…92 Most very old individuals with severe dementia in the community die away from usual place of residence, and hospitals remain the most common place of death. 93 Ideally, health and social care professionals should discuss preferences with the person with dementia while they still have capacity and record advance care planning statements, advance decisions to refuse particular treatments, preferred place of care in future and lasting power of attorney. 87…”
Section: Palliative Carementioning
confidence: 99%
“…Characteristics of residents in this study, in terms of age profile, morbidity, level of dependency and the need for end-of-life care reflect the characteristics of nursing home residents elsewhere including the UK 1. The findings from this study show that preferences for this profile of residents include limited medical interventions in the nursing home rather than the hospital, Do Not Attempt Resuscitation, and the nursing home as the preferred place of death.…”
Section: Commentarymentioning
confidence: 62%